Modifications and Performance Test of Semawar, Spiral and Tube Stove with Jatropha Fuel Oil - Fatah, Gatot S.A.; Soebandi, Soebandi; Hastono, Abi D. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2014)
Kerosene as the primary fuel for cooking, is relatively expensive (at Rp 8000.-/liter). Recently the pressure cooker kerosene is still used by cake makers, bread, and noodle. By modifying the part of the cup rubbing alcohol and add a protective piping hot, the stove can be used with pressurized fuel Jatropha oil. Tobacco industry, ceramic and asphalt still use the stove.The purpose of this study is to obtain a prototype pressure cooker (semawar, spiral and tube type) fueled with jatropha oil by modifying the part of the reservoir cup rubbing alcohol, pipe and nozzle heat shield oil expenses. Modified pressure cooker and test performance using Jatropha oil is obtained as follows: the fuel consumption of 935 - 1250 mL/hour; pre-heating 9-17 minutes; time required to boil 2 liters of water was 5 minutes; noise level of 75.5 – 88.2 dB and the reddish color of blue flame.Keywords: pressure stove, oil, jatropha